Persepsi Orang Tua dan Pengasuh terhadap Pemberian Imunisasi Rutin pada Balita Pasca Pandemi Covid-19 - Dian Kusumaningtyas; Rahma Dian Hanifarizani (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2024)
Immunization is an effective strategy of the government to reduce morbidity and mortality from Preventable Diseases by Immunization (PD3I). During the Covid-19 pandemic, this situation had a significant impact on the health sector, reducing immunization coverage rates. Currently, Indonesia is in the post-Covid-19 pandemic phase characterized by positive trends in pandemic control. This study aims to understand the perceptions of parents or caregivers regarding the provision of routine immunization to children in the post-Covid-19 pandemic era. The research method used a cross-sectional design with sampling using the quota sampling method, with a total of 100 respondents. Data were collected through a questionnaire adopting the health belief model theory to parents or caregivers who brought their children to the Posyandu for immunization. The results showed that perceptions of vulnerability (p value = 0,071), seriousness (p value = 0,121), and cues to action (p value = 0,731) had an insignificant effect on immunization for toddlers, while perceptions of benefits (p value = 0,008), barriers (p value = 0,000), and self-efficacy (p value = 0,000) had a significant effect on immunization for toddlers in the post-Covid-19 pandemic era (p value < 0.05). The components of the health belief model that form the perceptions of parents or caregivers towards immunization are interconnected, although not all are statistically significant. Therefore, perceptions of vulnerability, seriousness, and cues to action need to be improved to form a good perception of immunization after the Covid-19 pandemic